Fifth British International Print Biennale. - International Print Biennale Bradford 1976; Diamond, Michael; Fuller, Peter; Wilson-Town, Kate (Bradford : Cartwright Hall, 1976)
Abularach ; Ackroyd, Norman ; Adair, Hilary ; Ado ; Ahlgren, Lauri ; Ahonen, Eino ; Alapfy, Andras ; Altwerger, Sandra ; Alviani, Getulio ; Amano, Junji ; Amimoto, Tomoyo ; Anderle, Jiri ; Anderson, Robert ; Andrew, David ; Anker, Suzanne ; Arita, Akiko ; Arnold, Dieter ; Baartman, Hendrik ; Baer, Peter ; Baines, Alan ; Balakjian, Marc ; Banerjee ; Barrera, Alberto ; Becker, Harald ; Beckley, Keith ; Beer, Richard ; Bejar, Feliciano ; Berlinicke, Harmut R. ; Bixby, Dick ; Böckman, Bengt ; Boga, Johanna ; Bosman, Lettie ; Boumans, Bart ; Brandt-Möller, Svend ; Brown, Ian ; Camnitzer, Luis ; Camporeale, Sergio ; Capobianco, Domenick ; Caulfield, Patrick ; de Chamay, Cojette ; Chantry, Melvyn ; Chaplin, Bob ; Cirulis, Karlis ; Clucas, Graham ; Cohen-Gan, Pinchas ; Colby, Stephen ; Collier, Brian ; Combs, Bruce Mc ; Comstedt, Maud ; Copello, Francisco David ; Cortright, Steven ; Cotten, Walter ; Cox, Lizzie ; Cugat, Delia ; Cuprys, Jacek ; Currell, Anthony ; Cynke, Anna Monika ; Davila, Carlos ; Davis, Michael ; Deck, François ; Dembo, Aleksandrs ; Demirli, Oya ; Denny, Robyn ; Descombes, Roger ; Downing, Holly ; Dunn, alf ; Durkin, Jennifer B. ; Duttweiler, Bernard ; Ebert, Gerda ; Edwards, Jeffrey ; Eirich, Gebhard M. ; Exall, Michael Roy ; Ezergaile, Dzidra ; Feldman, Paul ; Fiocchi, Lino ; Fleischer, Karin ; Fong, Freddie ; Fossick, Michael ; Freiles, Antonio ; Frigge, Adri ; Fukasawa, Shiro ; Funasaka, Yoshisuke ; Furnival, John ; Galantai, Gyorgy ; Gluck, David ; Gongora, Leonel ; Gosling, Ambrose David ; Goto, Hajime ; Grabowski, Jerzy ; Gracia, Carmen ; Green, Alan ; Hall, Nigel ; Hanrahan, Barbara ; Hanspers, Olle ; Hara, Takeshi ; Haselwanger, Karl-Heinz ; Hayashi, Hiroyuki ; Hedegaard, Peter ; Helmuts, Inars ; Herbulot, Katia ; Heske, Marianne ; etc.
Fifth British International Print Biennale, City of Bradford Metropolitan Council Art Galleries and Museums, Bradford, 13 June - 12 September 1976
Engels
kunstcatalogus